Efficacy of segmental re-examination of proximal colon for adenoma detection during colonoscopy: a randomized controlled trial - Guo, Chuan-Guo; Zhang, Feifei; Ji, Rui; Li, Yueyue; Li, Lixiang; Zuo, Xiu-Li; Li, Yan-Qing (Endoscopy, 2017)
Background and study aims Interval colorectal cancers detected after screening colonoscopy are more likely to be associated with missed lesions in the proximal colon. The aim of this study was to determine whether segmental re-examination of the proximal colon could increase the proximal adenoma detection rate (ADR) and to evaluate the time-effectiveness of this approach.Patients and methods Patients undergoing colonoscopy were recruited into the prospective randomized controlled study. They were randomly assigned to the segmental re-examination group, in which the proximal colon was examined twice segmentally, and a control group in which the withdrawal time was extended (EWT). Detection rates were calculated and compared for all polyps and adenomas in both the proximal colon and the whole colon. Withdrawal times were recorded and compared.Results A total of 360 patients were included in the study (re-examination 178 vs. EWT 182). The proximal ADR in the re-examination group was higher than that in the EWT group (33.1 % vs. 23.6 %; P = 0.045). More proximal adenomas were detected per patient in the re-examination group (0.54 vs. 0.36; P = 0.048). The ADR of the whole colon was similar in the two groups. Proximal withdrawal time was also similar (re-examination 4.29 ± 1.23 minutes vs. EWT 4.34 ± 1.36 minutes; P = 0.74). In addition, there was no statistically significant difference in the total duration of the colonoscopy between the two groups.Conclusions Segmental re-examination of the proximal colon increased the proximal ADR and the number of proximal adenomas detected, and was accomplished easily and safely without increasing the overall examination time.Trial registration: ClinicalTrials.gov (NCT02581475)